Formulation and in-vitro functional evaluation of a Bacillus-based multi-strain probiotic consortium relevant to protein-energy malnutrition - Priya Mori; Ishita Modasiya; Mehul Chauhan; Hina Maniya; Vijay Kumar; Apurba Kumar Sarkar (PLoS ONE, 2026)
Protein-energy malnutrition (PEM) remains a critical global health challenge, characterized by impaired nutrient absorption and chronic gut inflammation. While probiotics offer a potential therapeutic avenue, the efficacy of single-strain interventions is often limited. This study aimed to formulate and evaluate a Bacillus -based multi-strain probiotic consortium (MSPC) specifically tailored for PEM. Three strains— Bacillus spizizenii BAB 7915, Bacillus tequilensis , and Bacillus rugosus -were selected based on their non-antagonistic, synergistic growth profiles. The MSPC demonstrated superior functional attributes compared to individual strains, exhibiting significant proteolytic activity (0.52 ± 0.03 U/mL) and robust anti-inflammatory potential (5.33 ± 0.06 U/mL). Additionally, the consortium showed high tolerance to gastrointestinal conditions and strong antioxidant properties. These results suggest that the MSPC can effectively enhance protein hydrolysis and mitigate gut inflammation, providing a scientifically validated, low-cost formulation for the nutritional rehabilitation of PEM patients.